Shading simulation for two photovoltaics solar generation residential systems (SPV) using SAM (System Advisor Model) - Nolasco, Daniela; Solís-Chaves, J.S. (TECCIENCIA, 2021)
In this document, shading models are developed for photovoltaic solar generation systems located in two environments, a rural one, in the Cundiboyacense savanna, and the other one within the con-urban area of the Colombian capital. Both systems consider a typical electrical load for an average house. The photovoltaic generation systems and their components are dimensioned based on this estimation, for which, in this case there are not considered battery banks. Shading on the panels is done using SAM, inserting objects of considerable height in both environments. The results of this modeling confirm that indeed, power losses are greater when considering the area of panels affected by shade. Therefore, a comparative simulation case is presented for the two considered environments, including and excluding losses due to the effect of shading, and the respective conclusions are written.